Strategi dan Metode Dakwah Walisongo - Hatmansyah, S.Ag., ME (Al-Hiwar : Jurnal Ilmu dan Teknik Dakwah, 2015)
Walisongo believed to be laying the first stone of Islam in Java. Gait Walisongo the map Da’wah of Islam in Indonesia in general and on the island of Java in particular is indeed an indisputable historical fact. The success da'wah Walisongo is inseparable from the role srtategi and the methods they employ. The strategy that is First Division Da’wah Region. The Walisongo in preaching activities, among others, is taking into account the strategic region. Second, the system of Da’wah carried out with the introduction of Islam through persuasion oriented penaman Islamic faith yan adapted to the situation and conditions. Third, is to conduct an ideological war to eradicate the ethos and values of dogmatic ang contrary to the Islamic faith, in which the scholars have to create myths and new counter values are incompatible with Islam. Fourth, is to approach the figures that are deemed to have influence somewhere and trying to avoid conflict. Fifth, trying mengguasai basic needs that are needed by the community, both the needs that are materially and spiritually.